Colonization and divergence: phylogeography and population genetics of the Atlantic coast beach mice. Issue 8 (17th November 2018) - Kalkvik, Håkon M.; Stout, I. Jack; Hoffman, Eric A.; Parkinson, Christopher L.
Abstract : Barrier island taxa provide an opportunity to investigate recent evolutionary processes, such as colonization and isolation of recently diverged taxa, and provide important insights into understanding contemporary diversity and the assessment of conservation units. Using rapidly evolving genetic markers (mitochondrial DNA and microsatellites), we studied the Atlantic coast beach mouse subspecies ( Peromyscus polionotus decoloratus, P. p. niveiventris, and P. p. phasma ). Our data indicate that each of the extant coastal subspecies ( P. p. niveiventris and P. p. phasma ) is comprised of unique haplotypes indicative of their isolation, while the extinct subspecies, P. p. decoloratus, contain a single haplotype, which was shared with P. p. phasma . Moreover, all the coastal haplotypes originate from a single mainland haplotype found in central Florida, USA. The microsatellite data indicated high levels of genetic structure among our sampled populations. Additionally, these data group the populations into three distinct genetic clusters, with each of the extant coastal subspecies belonging to their own cluster and the mainland individuals forming a separate cluster. The extant Atlantic coast beach mice are on separate evolutionary trajectories, thus representative of separate taxonomic units. Therefore, the data support that two extant subspecies on the Florida Atlantic coast fit the Distinct Population Segment designation and should be managed and conserved as two separate independent units.